Historical Origins of the International Law Doctrines in Latin America (XIX-XX centuries) - M. V. Golubeva (Московский журнал международного права, 2023)
INTRODUCTION: The expansion of the community of states with independence of former European colonies in Latin America was a new historical fact that contributed to the evolution of international law. On the basis of Latin American doctrinal thought and international diplomatic practice the principles enshrined today in universal international legal acts were proclaimed. International law is often viewed from a Eurocentric point of view, with such a position little attention is paid to the influence of Latin American doctrine on the development of international law at the universal level. Therefore, it seems appropriate to highlight the question - in a historical retrospective - about the contribution of Latin American states to the formation of international law and international legal consciousness.MATERIALS AND METHODS: The materials for the study were the international legal norms of universal and regional nature, the works of national and Latin American scientists. When writing the article, general and particular scientific methods were used, namely, deduction and induction, analysis and synthesis, the historical method.RESEARCH RESULTS: The article reveals the origins of the doctrines of international law developed by Latin American authoritative international lawyers, state and political figures in the XIX-XX centuries. These doctrines had a significant impact on the formation and development of international law not only in the Latin American region, but also in the world as a whole, influenced the development of positions of Latin American states in the international arena.DISCUSSION AND CONCLUSIONS: The article substantiates the conclusion that it is necessary to consider modern international law, taking into account the significant contribution of Latin American states to its evolution at the universal level; reveals the interconnection of the principles in the doctrines of Latin American lawyers and state figures that were included in the system of international law at the universal level.